Classroom management creating a successful k-12 learning community - Burden, Paul R. (Wiley, 2017)
"A practical guide to what can be accomplished utilizing the technical aspects of Classroom Management, this invaluable resource will not only help educators learn how to build positive classroom communities, but also outline methods for involving students in the creation of their learning environment. The Sixth Edition has been updated to include a new chapter on communication skills for teaching, incorporated classroom case studies in each chapter, and includes updates using the latest management research in several chapters."--Provided by publisher.